Labor Pain, Analgesia, and Postpartum Depression: Are We Asking the Right Questions?. Issue 3 (September 2020) - Lim, G.; Levine, M.D.; Mascha, E.J.; Wasan, A.D.
Abstract : ( Anesth Analg . 2020;130:610–614) The major life events of pregnancy and postpartum recovery are known to be capable of triggering depression, anxiety, and adjustment disorders. As acute pain has also been linked to depression (as a risk factor for persistent postsurgical pain), questions have been raised regarding labor pain, epidural analgesia (EDA), and their link to depression. The authors of the above study interpreted findings of a longitudinal cohort study (which comprised 1503 pregnant women in Sweden) by utilizing conceptual path analysis. The analysis held Edinburgh Postnatal Depression Scale of ≥12 at 6 weeks postpartum as the primary outcome, with the use of EDA as the primary predictor of interest. A directed acyclic graph was used to assess the relationship between EDA and postpartum depression (PPD), as this type of diagram displays all variables of interest and their hypothesized relationships (with a stipulation of unidirectional relationships indicating causation in the direction of the arrow).